Spacer-length DNA intermediates are associated with Cas1 in cells undergoing primed CRISPR adaptation. Issue 6 (15th February 2017) - Musharova, Olga; Klimuk, Evgeny; Datsenko, Kirill A.; Metlitskaya, Anastasia; Logacheva, Maria; Semenova, Ekaterina; Severinov, Konstantin; Savitskaya, Ekaterina
Abstract: During primed CRISPR adaptation spacers are preferentially selected from DNA recognized by CRISPR interference machinery, which in the case of Type I CRISPR–Cas systems consists of CRISPR RNA (crRNA) bound effector Cascade complex that locates complementary targets, and Cas3 executor nuclease/helicase. A complex of Cas1 and Cas2 proteins is capable of inserting new spacers in the CRISPR array. Here, we show that in Escherichia coli cells undergoing primed adaptation, spacer-sized fragments of foreign DNA are associated with Cas1. Based on sensitivity to digestion with nucleases, the associated DNA is not in a standard double-stranded state. Spacer-sized fragments are cut from one strand of foreign DNA in Cas1- and Cas3-dependent manner. These fragments are generated from much longer S1-nuclease sensitive fragments of foreign DNA that require Cas3 for their production. We propose that in the course of CRISPR interference Cas3 generates fragments of foreign DNA that are recognized by the Cas1–Cas2 adaptation complex, which excises spacer-sized fragments and channels them for insertion into CRISPR array.